Seed Health Status of Farmer Seed Samples vs Certified Samples of Rice Varieties in Andhra Pradesh - K.V.S. MEENA KUMARI; B. RAJESWARI; P.S. RAO (Seed Research, 2026)
Experiments were conducted to asses the health status of farmer's vs certified seed samples of rice in Andhra Pradesh. Farmer's samples (271) and certified samples (30) were analysed for seed quality status in laboratory and disease incidence in field conditions during kharif 2002-2004. The occurrence of seed borne fungi Drechslera spp (2.2%) was maximum in farmer samples over certified samples (0.5%). In addition to Drechslera oryzae, Fusarium monliforme, Curvularia lunata, Aspergillus flavus, Cheatomium, Alternaria spp were recorded in both the samples. The germination percentage and seedling vigour decreased in farmer's samples (88 to 90%), (607) over certified samples (89 to 92%) and (698) indicating the poor seed quality status of farmer's samples. The incidence of seed borne disease viz., BLB, brown spot, narrow brown leaf spot and sheath rot were higher in farmer's samples (1-5 scale) than in certified seed samples (1-3 scale).